HEALTH PROMOTION BY TEACHING DUAL TASK EXERCISE AND EMPOWERING CADRES ON GAIT IMPROVEMENTAS WELL AS THE BALANCE OF THE ELDERLY IN GOWA REGENCY - Erawan, Tiar; Agussalim, Agussalim; Nugraha, Rahmat (Yayasan Education and Social Center, 2023)
Walking and balance disorders are the most common causes of falls in the elderly and often lead to injury and disability, Gait and balance disorders are usually multifactorial and require a comprehensive examination to determine contributing factors and appropriate interventions. Most of the gait changes that occur in the elderly are related to underlying medical conditions, walking and balance disorders should not be viewed simply as inevitable consequences of aging. Early identification of gait and balance disorders and determination of appropriate interventions can prevent dysfunction and loss of independence. This community service is carried out in Gowa Regency, South Sulawesi Province. The intervention given to the elderly is to provide and teach how to carry out dual task exercise interventions in postural control, carry out health promotion and empowerment of cadres are given in the right way and carried out continuously to improve the gait and balance of the elderly in Gowa Regency